1991
DOI: 10.1073/pnas.88.17.7711
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutations of Dictyostelium actin: disruption of a negative charge cluster at the N terminus.

Abstract: Aspartic acid residues in the N-terminal negative charge cluster of Dictyostelium actin were replaced with histidine residues by site-directed mutagenesis of the actin gene. The mutant actins were expressed in Dictyostelium cells and were purified to homogeneity by HPLC. Functional properties of the mutant actins were compared with those of the wild-type actin. (i) In vitro assays of the sliding movement of actin filaments driven by myosin showed that the movement was slowed by the mutations.(ii) The mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 33 publications
3
113
2
Order By: Relevance
“…The reason for using this actin gene is that the N-terminal sequence of actin has been shown to be important for its function such as the interaction with myosin (29). Furthermore, the Tetrahymenaactin has only about 75%homologyto conventional actin and has been shown to display several unusual features (6) To see if the exogenous actin gene(s) has actually been introduced in the genome of these clones, the genomic DNAfrom each clone was analyzed by Southern hybridization using a fragment of the cloned genomic actin gene as a probe (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for using this actin gene is that the N-terminal sequence of actin has been shown to be important for its function such as the interaction with myosin (29). Furthermore, the Tetrahymenaactin has only about 75%homologyto conventional actin and has been shown to display several unusual features (6) To see if the exogenous actin gene(s) has actually been introduced in the genome of these clones, the genomic DNAfrom each clone was analyzed by Southern hybridization using a fragment of the cloned genomic actin gene as a probe (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the replacement of loop 2 with noninserted and B2-inserted sequences of human nonmuscle MHC-IIB added one and three more net negative charges compared with the wild type, respectively. The increase of the negative charges could be responsible for the reduction of the affinity for F-actin in Dic-B and Dic-B2 by repulsion of the N-terminal negative charges of actin (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Modification of the charge environment at the N terminus by either tag could affect these ionic interactions and interfere with the normal cross-bridge formation. Moreover, it has been shown that mutations in the N-terminal region of actin, which yielded a change of charge, affect myosin S1 binding to actin and thereby reduce in vitro motility (Aspenström and Karlsson, 1991;Aspenström et al, 1992;Sutoh et al, 1991;Miller et al, 1996). However, N-terminal mutations that do not induce charge changes may also affect actomyosin interactions.…”
Section: Tags At the N Terminus Of Actin May Influence Actin-myosin Imentioning
confidence: 99%